Toward an accurate assessment of tourism economic impact: A systematic literature review - Anyu Liu; Yoo Ri Kim; Haiyan Song (Annals of Tourism Research Empirical Insights, 2022)
Tourism is acknowledged as a contributor to destination economies in many countries. However, COVID-19 has devastated the tourism industry in numerous national economies. Although the economic impact of tourism on destinations has been examined in a large body of tourism literature, most studies have utilized the tourism-led economic growth hypothesis and traditional methods and data rather than cutting-edge economic methods. This study conducts a systematic literature review on tourism economic impact between 1975 and 2020, analyzing the general bibliometrics and examining the key themes and methods of assessing tourism economic impact. It contributes to an accurate assessment of tourism economic impact, works to identify gaps in the literature, highlights emerging trends in the field, and proposes directions for future research.
Keywords: 330; Tourism economic impact; Tourism development; Economic impact; Economic development; Economic growth